UPAYA MENINGKATKAN KEMAMPUAN GURU SMP NEGERI NUBA ARAT KECAMATAN KANGAE DALAM MENGELOLA PEMBELAJARAN MELALUI SUPERVISI KLINIS PADA SEMESTER GENAP TAHUN PELAJARAN 2018/2019 - ANGELINUS WONGGA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Teachers at the SMPN Nuba Arat District Kangae Sikka District, 76.68% was a new teacher and energy Honorer. Preliminary supervision results show teachers teaching by promoting lectures. Whereas the demands of the 2013 curriculum, in the process of learning in the classroom using step 5M is observing, Minister, collecting information/trying, menalar/associating. Therefore, in ensuring the implementation of the principal task teachers E-ISSN 2686 5661 VOL.01 NO. 12. JULI 2020 INTELEKTIVA : JURNAL EKONOMI, SOSIAL & HUMANIORA 28 ANGELINUS WONGGA must be supervised. Clinical supervision is a form of professional guidance given to the teachers based on their needs through a systematic cycle of planning, careful observation of the implementation and assessment of the results of the observation immediately and objectively about the teaching appearance. The clinical supervision cycle corresponds to a cycle in school action Research (PTS), each cycle consists of four phases of activity i.e. planning, implementation, observation, and Reflection (Arikunto, 2011). This PTS is held in the even semester of lesson 2018/2019 for 4 months which is from the second week of January to the second week of May 2019, with a target of 19 teachers of subjects. PTS are conducted in two cycles, and are declared successful when the average achievement of each indicator > 80%. The results of the pre-vision cycle acquired data 1) teacher's ability to compile RPP is 47.37% (very less) and 2) teachers ' ability in the learning process according to the curriculum 2013 is 35.79% (very less). Through mentoring in cycle I, obtained the average achievement of pedagogic competence teachers in: 1) drafting RPP is 62.41% (less) and 2) learning process According to curriculum 2013 is 51.05% (good). Thus the study was declared successful, and it can be concluded that through clinical supervision can improve the competency of SMPN teachers Nuba Arat in conducting learning based on curriculum 2013 at the even semester of lesson 2018/2019.